Aptamers for CD Antigens: From Cell Profiling to Activity Modulation - Amin Nozari; Maxim V. Berezovski (Elsevier, 2017)
Nucleic acid-based aptamers are considered to be a promising alternative to antibodies because of their strong and specific binding to diverse targets, fast and inexpensive chemical synthesis, and easy labeling with a fluorescent dye or therapeutic agent. Cluster of differentiation (CD) proteins are among the most popular antigens for aptamers on the cell surface. These anti-CD aptamers could be used in cell biology and biomedicine, from simple cell phenotyping by flow cytometry or fluorescent microscopy to diagnosis and treatment of HIV/AIDS to cancer and immune therapies. The unique feature of aptamers is that they can act simultaneously as an agonist and antagonist of CD receptors depending on a degree of aptamer oligomerization. Aptamers can also deliver small interfering RNA to silence vital genes in CD-positive cells. In this review, we summarize nucleic acid sequences of anti-CD aptamers and their use, which have been validated in multiple studies. Keywords: aptamers, cluster of differentiation, siRNA, cell imaging, drug delivery